PENGEMBANGAN MATERI MUATAN LOKAL DI SEKOLAH MENENGAH ATAS 1 BATURITI - Dharmawan, I Made; Mandiasa, I Nyoman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Education plays an important role in developing human resources and developing a whole person. Learning programs and educational programs are contained in an educational material program guide called the curriculum. The current curriculum in Indonesia is called the 2013 Curriculum. The 2013 curriculum applies comprehensively and integrally in education levels both at the primary level and education at the general secondary level (SMA) or vocational secondary education (SMK). The curriculum is outlined in more detail and is more immersive in the syllabus. The syllabus is arranged by the center, according to the students' conditions and abilities. The syllabus is compiled and detailed and developed in the form of an RPP (Learning Implementation Plan). In relation to the authority that schools have over the development of local content, SMA N 1 Baturiti develops local content skills for making burials for female students and weaving skills for male students. The theory used in this research is the theory of hegemony, social capital theory and constructivist theory. This type of research in order to obtain all the necessary data used qualitative research with qualitative descriptive methods, while the data collection technique was through document study interviews obtained from Hindu religious teachers and students of SMA N 1 Baturiti. From the results of the analysis, it is found that the efforts to develop local content at SMA N 1 Baturiti are the development and deepening of the syllabus of Hindu Religion subjects, especially in the field of Hindu religious ceremonies. related to Hinduism for male students